The effects of labor supply shocks on labor market outcomes: Evidence from the Israeli-Palestinian conflict - Hani Mansour (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Since September 2000, as a result of mobility restrictions, the supply of Palestinian workers competing for local jobs in the West Bank has increased by about fifty percent. This paper takes advantage of this unique natural experiment to study the effects of labor supply shocks on labor market outcomes. Using quarterly information on wages and employment in each city in the West Bank, the paper analyzes the short-run adjustment of labor markets to a large inflow of workers separately from the effects of political instability. The results suggest that low-skilled wages are adversely affected by an increase in the supply of low- and high-skilled workers, while high- skilled wages are only weakly negatively related to an increase in their own supply. This is consistent with a scenario in which high skilled workers compete for low skilled jobs, pushing the low skilled into unemployment. This latter hypothesis is confirmed by analyzing the effects of changes in labor supply on unemployment.
Keywords: J61; J21; D74; C21; 330; Immigration; labor supply shocks; border controls; Arbeitsangebot; Schock; Migrationspolitik; Beschäftigungseffekt; Qualifikation; Lohn; Ungelernte Arbeitskräfte; Arbeitslosigkeit; Westjordanland; Palästina